O direito superveniente nos recursos extraordinário e especial - Silveira Neto, Antônio Gonçalves da Mota (2009)
This present study focus on the supervenient law in the exceptionals petitions both “ extraordinário” and “ especial” . However, it is known that there are imposed limits that are included in the prequestioning and also the lawsuit, determined by specific moment of the process when analyzing the subjective elements and the objective elements, that must remains unchangeable. That way, the exceptional petitions can establish, first of all what is the most relevant, then the peculiarities and hypothesis that fits. It is also important to understand the subject to find elements which identify lawsuit, that is the triple identity and also the establishment of the lawsuit, genesis e use nowadays. After all, it is a way of searching searching an ideal system for this approach. At the end, the objective is to bring up together the institute representative, so that the two different areas in a litigation, respecting even the contradictory terms, the law act and also the right acquired, which can be a benefit of the ius superveniens